A Competing Risk Analysis of Women Dying of Maternal, Infectious, or Non-Communicable Causes in the Kintampo Area of Ghana - Abubakari, Sulemana Watara; Badasu, Delali Margaret; Apraku, Edward Anane; Amenga-Etego, Seeba; Asante, Kwaku Poku; Bawah, Ayaga Agula; Owusu-Agyei, Seth (Frontiers in Global Women's Health, 2021)
Abstract Introduction: Maternal, infectious and non-communicable causes of death combine to be simultaneously a major health problem for women of reproductive age (WRA) in sub-Saharan Africa. Not much is known about the relative risk of each of them when considered together and their demographic impacts. The focus of studies on WRA has been on maternal health. The evolving demographic and health transitions in low-and middle-income countries suggest a need for a comprehensive approach to resolving women’s health challenges beyond maternal causes. Methods: Deaths and person-years of exposure were calculated by age for WRA 15-49 years of age in the Kintampo Health and Demographic Surveillance Systems area from January 2005 to December 2014. Causes of death were diagnosed using a standard verbal autopsy questionnaire and the 10th Revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-10). Identified causes of death were categorized into three broad areas: maternal, infectious and non-communicable diseases. Multiple decrements and associated single decrement life table methods were used. Results: Averting any of the causes of death was seen to lead to improved life expectancy, but eliminating infectious causes of death leads to the highest number of years gained. Infectious causes of death affected all ages and the gains in life expectancy assuming they were eliminated diminished with increasing age. The oldest age group, 45-49, had the greatest gain in reproductive aged life expectancy if maternal mortality were eliminated. Discussion: This study demonstrated the existence of a triple burden. Infectious causes of death are persistently high whilst deaths from non-communicable causes are rising and the level of maternal mortality is still unacceptably high. It recommends that attention should be given to all the causes of death among women of WRA.